COMMUNITY BASED ANALYSIS ON MANGROVE FOREST CHANGES IN REMBANG DISTRICT, CENTRAL JAVA PROVINCE - Mochamad Budi Purnomo; Dyah R. Hizbaron; Michiel Damen (Jurnal Kependudukan Indonesia, 2015)
Mangrove forest is widely known as valuable resources, which provide goods and services as well as its function to protect coastal area from coastal erosion and promote sedimentation. This study aims to investigate community perspective towards dynamic change of mangrove forest due to coastline change. The research highlights two observations, i.e 1) coastline detection using visual interpretation; 2) community observation towards mangrove forest. Semi-structured questionnaire was applied to analyze the influence of mangrove forest changes to community as well as their adjustment. A proportional random sampling protocol was performed to determine 81 respondents from the village of Pasarbanggi, Tasikharjo and Tunggulsari. The research reveals that the research area exposes to coastline change, which induces mangrove forest dynamic. The dynamic mangrove forest influences local adaptation strategies, and it corresponds to government intervention within mangroves program. Pasarbanggi Village, which received various programs, both from government and other parties, combined with active participation of local people in establishing mangrove, has a stable increase of mangroves area between periods without significant disturbances compared to Tasikharjo Village and Tunggulsari Village. In line with this situation, respondents have different response toward the changes of mangrove forest in their area. Respondents’ response toward mangrove forest changes correlates to their participation in government mangroves program. Respondents in Pasarbanggi Village are apparently more benefited by the changes of mangroves forest including direct and indirect benefit from the forest, as well as from mangroves program, compared to another respondents in Tasikharjo Village and Tunggulsari Village.